Role of physico-chemical properties of the soil in badlands forming processes around Chitrakoot, India - Singh N.; Jha M.; Tignath S.; Singh B.N.; Chattopadhyay A. (My University, 2025)
Eco-restoration attempts in badlands are generally not fully successful because physical solutions such as reshaping and leveling of gullies and ravines to check erosion and soil losses prove to be temporary in nature. In this context, it leads to conceptualization that the cause of badland formation is not merely topographical but should be related to changes in the intrinsic properties of soils. There is a lack of understanding as to the formative role of physico-chemical characteristics of soils in the formation of badlands. The objective of our study is to determine such critical physico-chemical characteristics of soils that are responsible for the onset of a self-aggravating erosive network of badlands by undertaking a case-study of part of the Mandakini River watershed, Chitrakoot, India. Standard IS codes were followed in determining these properties. These soils have a silt-loam texture with high bulk density. Depletion of clays lowered Atterberg limits which consequently rendered the soils unstable even at low values of moisture content. The overlay analysis of these properties and drainage frequency shows perfect superimposition in categorizing badlands into zones of the severity of degradation. The chemistry of these soils has low sodium, high calcium with the presence of calcretes, low organic matter, and a low amount of illites and are mostly alkaline. The outcome of the study is helpful in understanding mutual interdependence between soil characteristics and processes of badlands that led to the intensification of rills-gullies-channels network. The findings would be useful in land management planning. © 2022 John Wiley & Sons, Ltd.